2022
DOI: 10.3389/fnagi.2022.816100
|View full text |Cite
|
Sign up to set email alerts
|

Aging Affects Subcortical Pitch Information Encoding Differently in Humans With Different Language Backgrounds

Abstract: Aging and language background have been shown to affect pitch information encoding at the subcortical level. To study the individual and compounded effects on subcortical pitch information encoding, Frequency Following Responses were recorded from subjects across various ages and language backgrounds. Differences were found in pitch information encoding strength and accuracy among the groups, indicating that language experience and aging affect accuracy and magnitude of pitch information encoding ability at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…This extension offered the potential explanation for the inconsistency observed in prior research. On one hand, past literature consistently indicated a decline in older adults' acoustic information processing (Clinard et al, 2010;Liu et al, 2022;Palmer & Musiek, 2014;Snell & Frisina, 2000). On the other hand, previous research showed that older adults generally maintained a proficiency level in comprehending spoken sentence discourse (e.g., Ayasse et al, 2017Ayasse et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extension offered the potential explanation for the inconsistency observed in prior research. On one hand, past literature consistently indicated a decline in older adults' acoustic information processing (Clinard et al, 2010;Liu et al, 2022;Palmer & Musiek, 2014;Snell & Frisina, 2000). On the other hand, previous research showed that older adults generally maintained a proficiency level in comprehending spoken sentence discourse (e.g., Ayasse et al, 2017Ayasse et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…As people age, they often experience diminishing capabilities, including reduced acoustic sensory capability, neurophysiological changes, and decreased cognitive functioning, which consequently impact listeners' ability to process temporal and spectral cues (e.g., McGarrigle et al, 2021;Murman, 2015;Tagliabue & Mazza, 2021). Compared with younger listeners, normal-hearing older adults generally have higher detection thresholds and lower accuracy in discriminating sound durations and frequencies (Clinard et al, 2010;Liu et al, 2022;Palmer & Musiek, 2014;Snell & Frisina, 2000). These age-related changes significantly impact older adults' accuracy in identifying vowels, consonants, and lexical tones (Fogerty et al, 2012;Y.…”
mentioning
confidence: 99%